2014
DOI: 10.1111/jfpe.12123
|View full text |Cite
|
Sign up to set email alerts
|

Alginate/PVA Beads for Levan Production by Zymomonas mobilis

Abstract: The levan is a biopolymer of great importance to the food industry since it is capable of defining and modifying the structure of one food, acting as stabilizer, thickener, gelling agent and being largely responsible for the texture of processed foods. The levan production by bacterial cell immobilization may potentialize the results of these studies, having advantages such as: high cell concentrations inside the reactor, increase the substrate absorption rate, improve the performance and reduce the risk of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The dripping process has been proved to be the most versatile technique to enable application of sodium alginate. Since this technique uses mild operational conditions, it is suitable for preserving thermolabile compounds, such as drugs, organisms, proteins or fragrances (Gaonkar et al, ; Gul & Dervisoglu, ; Lorenzetti, Moro, & García‐Cruz, ; Rakmai, Cheirsilp, & Prasertsan, ). Besides this technique has potential to be scaled up, due to its simplicity, the yield of beads production is high due to the low losses of material during the formation of bead (Oxley, ).…”
Section: Introductionmentioning
confidence: 99%
“…The dripping process has been proved to be the most versatile technique to enable application of sodium alginate. Since this technique uses mild operational conditions, it is suitable for preserving thermolabile compounds, such as drugs, organisms, proteins or fragrances (Gaonkar et al, ; Gul & Dervisoglu, ; Lorenzetti, Moro, & García‐Cruz, ; Rakmai, Cheirsilp, & Prasertsan, ). Besides this technique has potential to be scaled up, due to its simplicity, the yield of beads production is high due to the low losses of material during the formation of bead (Oxley, ).…”
Section: Introductionmentioning
confidence: 99%
“…The Zymomonas mobilis species is likely related to ethanol production; it showed a high performance in response to external stresses such as high ethanol concentration, high temperature, and harsh acidic fermentation conditions (Wang et al, 2016;Zhang et al, 2016). In addition, Zymomonas mobilis has anti-leukemic activity, antitumor effects, and prebiotic activity (Einsfeldt et al, 2016;Lorenzetti et al, 2015;Yoon et al, 2004). No Acetobacter was detected in this study, despite representatives of this genus have previously been isolated from other tibicos (Gulitz et al, 2011;Marsh et al, 2013).…”
Section: Resultsmentioning
confidence: 65%
“…It was reported that during continuous cultivation of Z . mobilis CCT4494, when immobilized in Ca- alginate gel the amounts of levan can range from 18.84 up to 112.53 g/L dependent on the incubation time [ 26 ]. Komagataeibacter xylinus , the producer of bacterial cellulose can also produce levan [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%